EKO-WISATA: SUATU ANALISIS EKONOMI SUMBERDAYA ALAM - M. Yuwana Marjuka (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
Ecotourism refers to tourists travelling to nature site because of the amenity and recreational value derived from having contact with some aspect of the natural world. One of the most attractive and preservative ecotourism destination at West Java area is Gunung Halimun National Park (TNGH). The traditional community at TNGH is named Kasepuhan Urug TNGH in the province of West Java is extremely rich in biodiversity. While ecotourism is a rapidly growing phenomenon, very much of this growth is unsustainable. This article reviews why this unsustainability arises and the poverty impact can be avoided. The first section sets out an economic model of ecotourism as the utilization of open access to renewable natural sites. This model is used to internalize the externalities factors of ecotourism activities. Externalities demonstrate how open access can lead to both economic and environmental inefficiency. The second section examines management solutions to the open access problem. This involves determining an owner of the site, either the state, or the local community, or a private group This owner must then choose policy instruments to restrict open access. This involves choosing between price and quantity instruments, deciding how to reduce rent dissipation and determining whether to restrict total numbers of tourists of damage done pertourist.